2021
DOI: 10.18357/jcs464202120123
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Child Care Participation Between Immigrant and Nonimmigrant Families

Abstract: This study used data from the Survey on Early Learning and Child Care Arrangements (SELCCA) and the Longitudinal Immigration Database (IMDB) to examine patterns of child care use among Canadian immigrant and nonimmigrant families. Overall, children from immigrant backgrounds were less likely to be in child care. When considering only those in child care, children from immigrant families were more likely to be in licensed care than those from nonimmigrant families. Parents of children with immigrant backgrounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Access to childcare programs enables full economic participation in the workforce (Obeng, 2007), yet the high cost and dearth of spaces in Canadian programs present as impediments to women's labour market participation (Findlay & Kohen, 2021; Mahon et al, 2012). The high cost of childcare has been found to disproportionately affect low‐income families and, correspondingly, new immigrant and refugee families often live in poverty (Kingsbury et al, 2021). A Canadian national survey confirmed that low‐income families were significantly more likely than other families to postpone a return to work or schooling when they experienced issues with childcare (Findlay & Kohen, 2021).…”
Section: Literaturementioning
confidence: 99%
“…Access to childcare programs enables full economic participation in the workforce (Obeng, 2007), yet the high cost and dearth of spaces in Canadian programs present as impediments to women's labour market participation (Findlay & Kohen, 2021; Mahon et al, 2012). The high cost of childcare has been found to disproportionately affect low‐income families and, correspondingly, new immigrant and refugee families often live in poverty (Kingsbury et al, 2021). A Canadian national survey confirmed that low‐income families were significantly more likely than other families to postpone a return to work or schooling when they experienced issues with childcare (Findlay & Kohen, 2021).…”
Section: Literaturementioning
confidence: 99%
“…Most studies on the use of formal childcare focus on differences between children in immigrant and non-immigrant families (Brandon, 2004;Kingsbury et al, 2021;Schober & Spiess, 2013), although recently there has been more attention to differences by country/region of origin (Biegel et al, 2021;Miller et al, 2013;Tervola, 2018), as well as focus on specific groups living in one (Röder et al, 2018) or several destinations (Wolf et al, 2020). Families' socio-economic background (education, employment status, income) tend to account for a large part of these differences, but other factors are also at play, such as distinct norms regarding child rearing or preference for caretakers who share the families' cultural background and/or language (Chaudry et al, 2011;Karoly & Gonzalez, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between children in immigrant and non-immigrant families in the use of formal child care services are observed across many destination countries: United States (Brandon, 2004;Miller et al, 2013) Canada (Kingsbury et al, 2021), Germany (Schober & Spiess, 2013), Ireland (Röder et al, 2018), Belgium (Biegel et al, 2021), Finland (Tervola, 2018), Sweden (Duvander 2006cited in Sainsbury, 2019. The disadvantaged socio-economic position of immigrant families in these contexts largely contributes to this gap.…”
Section: Introductionmentioning
confidence: 99%